Pengaruh Penggunaan Media Belajar Online Selama Pandemi - Unik Hanifah Salsabila; Siti Nurfajri Utami; Ashadatul Zahra; Fikri Haikal; Acep Cahyono (Peneliti.net, 2021)
Online learning is an option taken as an alternative to covid19. Technology is becoming much needed and useful in current pandemic conditions. In this article the research method used is the literary study method. Search, read, write, and conclude research results that have the same big themes through various books, articles, journals, and other sources. This research aims to determine whether or not the influence of online learning is influenced by online learning media implemented during pandemics. The results obtained from several studies show a positive and negative influence in the online learning process.